Baptists and slavery in frontier Missouri during the antebellum era - Woodward, Nathan, author; Knight, Fred, advisor; Gudmestad, Robert, committee member; Lindsay, James, committee member; Kim, Joon, committee member (Colorado State University. Libraries, 2011)
This thesis examines the way residents of the Missouri frontier viewed and reacted to slavery, with a particular emphasis on Missouri Baptist thought. I argue that Baptists were ambivalent toward slavery because of their religion and their unique agricultural position on the frontier far from the large cotton plantations of the Deep South. Their attitude toward slavery manifested itself in Frontier Baptist Conventions and within Baptist newspapers in Missouri. Because of this ambivalence, Baptist slaveholders and slaveholders in the largely Baptist town of Liberty, Missouri, had to find a way to reconcile their growing antislavery thoughts with their largely proslavery surroundings. Their answer came in the form of gradual emancipation of the slaves. Missouri Baptists sought to free and expatriate African Americans in colonization movements to Africa. To gauge these sentiments, this project relies heavily on three newspapers published in Missouri during the antebellum era: The Western Watchmen of St. Louis, The Liberty Tribune of Liberty, and The Border Star of Westport. The first is the only Baptist paper and the latter two are both secular. To ascertain their opinions on slavery, I used the papers to focus on ideas relating to the colonization movement, John Brown, Bleeding Kansas, states' rights, and secession. The final part of the thesis examines how southern Baptists reacted to the newly freed slave population during and after Reconstruction.